Preferences of Healthcare Professionals on 3D-Printed Tablets: A Pilot Study - Odelia Goh; Wei Jiang Goh; Seng Han Lim; Grace S. Hoo; Raymond Liew; Tat Ming Ng (MDPI AG, 2022)
An inaugural study was performed to understand the perceptions of healthcare professionals toward the potential benefits of 3D printing in Singapore. This study sought to increase awareness of 3D printing applications for viable clinical applications and to elucidate the current gaps in therapy where 3D printing could play a role. A common example would be the use of 3D printing to manufacture polypills, thereby reducing the daily pill burden of patients and possibly improving medication adherence. A qualitative descriptive survey with a single-centered cross-sectional design was performed at Tan Tock Seng Hospital, a tertiary referral hospital with 1700 beds. This study had a total of 55 respondents comprising doctors and pharmacists. Most of the respondents viewed the 3D printing of oral dosage forms favorably and agreed about the potential advantages this technology could offer. More than 60% of the respondents were also willing to prescribe 3D printed tablets to patients. Respondents' concerns were grouped into three main categories: formulation considerations, manufacturing processes, and administrative issues. Viewed in its entirety, this study provides a valuable starting point for understanding the perceptions of healthcare professionals in adopting 3D printing technology.